Full Waveform Inversion (FWI) in 3D Synthetic Geological Modelling - Indriati Retno Palupi; Wiji Raharjo; Oktavia Dewi Alfiani (Geological Agency, 2026)
Modeling the Earth's subsurface is important in geophysics, for example, tomography and Full Waveform Inversion (FWI). Especially for FWI, it is a method in the geophysical field that is used to describe the subsurface with a high-resolution image by utilizing all parts of observation data (seismic traces) based on a velocity model. In this paper, the 3D synthetic geological modelling was generated as an initial model; then, based on it, seismic traces and also shot gathers were simulated by arranging sources and geophones, and finally, the FWI was done. After seismic traces (assumed as acoustic wave equations), complete with the smoothness, were obtained, then a hyperbolic partial differential equation between the time and space domains was applied before entering the inversion process. During the inversion process, the final seismic traces were obtained by velocity updating in the entire space and time until they reached zero misfit, so wave propagation and the final velocity model could be observed. The pattern changes of seismic traces, shot gather, wave propagation, and FWI could be described by modifying the seismic source and geophone location in the geological model. However, by generating a 3D synthetic geological model, there is much flexibility for getting various descriptions of acoustic wave simulations.